World-wide barriers and enablers to achieving evidence-informed practice in education: what can be learnt from Spain, England, the United States, and Germany? - Malin, Joel R.; Brown, Chris; Ion, Georgeta; Van Ackeren, Isabell; Bremm, Nina; Luzmore, Ruth; Flood, Jane; Rind, Gul Muhammad (Humanities and Social Sciences Communications, 2020)
A global push exists to bolster the connections between research and practice in education. However, fostering evidence-informed practice (EIP) has proven challenging. Indeed, this ‘problem’ requires simultaneously attending to multiple aspects/levels of education systems, and to the contexts within which they reside. As such, comparative analyses using systems approaches hold potential for achieving context-specific insights regarding how to foster EIP. However, such analyses have been scarce, and what research does exist has generally been limited relative to methods and theory. Given this, the present study executes and describes/reflects upon a novel approach for analysing and comparing EIP in/across systems. In this study, educators’ evidence use patterns are described and comparatively analysed, using a sample of four regions within high-income national settings: Catalonia (Spain), England (UK), Massachusetts (USA), and Rheinland-Pfalz (Germany). This study employs a dual analytical frame (a cohesion/regulation matrix and institutional theory) to supply a methodological lens through which to understand EIP within and across these four systems. Together, this approach not only provides a way of accounting for the macro-level differences between contexts, it also enables a comparison of meso-level and micro-level factors (via institutional theory) that might be common and distinct across systems. This study’s findings reveal substantial diversity in the extent and nature of evidence use between systems, which in turn patterned according to distinctive cultural, systemic, and institutional features. Considering these findings, this study’s discussion advances some provisional insights and reflections regarding actual and potential EIP in education. For example, variability relative to the types/extents of accountability pressures, and how this affected educators’ data and evidence use, enabled a discussion holding relevance for policymakers. We also share process-related insights—i.e., describing the advances and challenges we experienced while undertaking this new approach. These points hold relevance for colleagues wishing to emulate and improve upon the efforts described herein, which we argue are applicable both in and beyond the education sector. Relative to education, these approaches can be applied and improved with an eye toward developing context-specific (vs. one-size-fits-all) packages for fostering EIP and, ultimately, achieving high quality and progressively improving schools/systems.
CRIS-Team Scopus Importer:2022-11-17